S100 calcium-binding protein A10 contributes to malignant traits in osteosarcoma cells by regulating glycolytic metabolism via the AKT/mTOR pathway. Issue 5 (2nd May 2022) - Ling, Feng; Lu, Qifeng
ABSTRACT: As an aggressive musculoskeletal malignancy, osteosarcoma (OSa) is popular among young adults and teenagers worldwide. S100 calcium-binding protein A10 (S100A10) functioned as a novel tumor-promoting protein in several human cancers. However, its role in OSa remains obscure. In this study, gene and protein levels were respectively determined by RT-qPCR or Western blotting. OSa cell proliferation, apoptosis, and metastasis were evaluated via CCK-8, colony formation, flow cytometry, and Transwell assays. To assess the glycolysis level, glucose consumption and lactate production were detected. It was found S100A10 was highly expressed in OSa tissues and cell lines. Besides, S100A10 facilitated proliferation and metastasis, and inhibited apoptosis in OSa cells. In addition, S100A10 regulated OSa cell proliferation, metastasis and apoptosis via mediating the glycolysis process. Furthermore, S100A10-mediated AKT/mTOR signaling accelerated glycolysis, thereby promoting malignant behaviors in OSa cells. Taken together, our findings indicated that S100A10 might promote malignant phenotypes of OSa cells by accelerating glycolysis and activating the AKT/mTOR signaling, providing a promising target for OSa treatment. GRAPHICAL ABSTRACT: uf0001